A further analysis of olfactory cortex development - Pedraza, María; De Carlos, Juan A. (Frontiers in Neuroanatomy, 2012)
The olfactory cortex (OC) is a complex yet evolutionarily well-conserved brain region, made up of heterogeneous cell populations that originate in different areas of the developing telencephalon. Indeed, these cells are among the first cortical neurons to differentiate. To date, the development of the OC has been analyzed using birthdating techniques along with molecular markers and in vivo or in vitro tracking methods. In the present study, we sought to determine the origin and adult fate of these cell populations using ultrasound-guided in utero injections and electroporation of different genomic plasmids into the lateral walls of the ventricles. Our results provide direct evidence that in the mouse OC, cell fate is determined by the moment and place of origin of each specific cell populations. Moreover, by combining these approaches with the analysis of specific cell markers, we show that the presence of pallial and subpallial markers in these areas is independent of cell origin.